Measurement of Specific and Non-Specific Parameters of Sampare Leaves Ethanol Extract (Glochidion sp var. Biak) as a Traditional Antimalarial Agent - Khairuddin Khairuddin; Burhanuddin Taebe; Olivia Indah Nathalya Kombong (STIFA Makassar, 2021)
Sampare (Glochidion sp var. Biak) is one of the Euphorbiceae family that has been used as traditional medicine. Empirically Papua society have used sampare as a folk remedy for malaria. The purpose of this study was establishing specific and non-specific standards of the ethanol extract of sampare leaves. The extract was obtained by maceration method using ethanol 70% with yield of 26,67%. Specific parameters include organoleptic observations such as, black brawny color, distinctive smell, and has a bitter taste. Furthermore, determine their alkaloids, flavonoids, tannins, quinones, and saponins. Chromatogram pattern indicates the presence of some stains and Rf values are different. The compound levels of water-soluble is 0.854%, while compound level of ethanol soluble is 0.385%. Nonspecific parameters include drying shrinkage content is 15.48%. The mass of extract is 0.895 g/ml. Water content was 4.56%, ash content was 7.62%, and total bacterial contamination was 1.66 x 102 CFU/ml and a total of mold contamination as much was 6.44 x 102 CFU/g.